Quantifying the mobile phone usage and gauging the perception about its harmful effects among the Otorhinolaryngologists in India- A questionnaire-based pan India survey - Anand, Prem; Varshney, Saurabh; Angral, Sumit; Sasanka, KSBS Krishna; Gupta, Pratima; Bhattacharya, Sudip (Indian Journal of Community Health, 2022)
Introduction-There is a definitive risk to human health because of mobile phones. The awareness towards mobile phones emitted electromagnetic radiation is of paramount importance to prevent health risks and possible negative health disorders. Aim and objectives-The aim of the survey is to assess the awareness of mobile phone radiation and its harmful effects on the body and the mobile phone usage trend among Otorhinolaryngologists from India. Methodology-The present survey aimed to obtain baseline data on cell phone usage and radiation awareness among a relatively homogenous cohort of Otorhinolaryngologists from India. This is a cross-sectional online survey assessing awareness of Mobile Phone radiation through a custom-made questionnaire devised by the authors which consisted of four parts: 1. Demographic details, 2. Mobile phone usage trend, 3. Knowledge of mobile phone radiation 4. Awareness of health hazards produced by mobile phone radiation. Results- The total number (n) of otorhinolaryngologists to whom the questionnaire was sent was 6336 of which 259 of them responded which formed the sample size of our study. Thus, the response rate of the survey was 4%. A total of 259 Otorhinolaryngologists participated in the study. The mean age of the population involved in the survey is 41.7810.32 years. The male-female ratio of the survey is 161:98 respectively. There were 172 private and 87 government ENT practitioners in the survey. MS otorhinolaryngology was the most common qualification of the study with 223 doctors having the degree, 20 having DNB, and 7 of them having completed DLO. The mean years of medical practice after postgraduation of the Otorhinolaryngologists participating in the questionnaire are 13.537.38 years. The major contributors to the survey were private ENT consultants with a count of 110, followed by Senior Residents 58, Assistant Professor 39, Professor 29, Associate professor 10, and Additional professor 13. It was evident from the questionnaire that 242 of the respondents were right-handed and 204 of the study population used their right ear for talking over the phone, it was also cross-checked by giving a miss call to them in close vicinity. The mean years of exposure to mobile phone usage by Otorhinolaryngologists are 15.01 5.75. A maximum of 153 surgeons were using mobile phones for 11-20 yrs. The average hours of daily mobile phone usage were 373 minutes. A highest of 101 Otorhinolaryngologists using mobile phones for >4 Hrs. Surprisingly through the questionnaire we came to know that a total of 60 doctors among the 250 use the phone daily for an average of more than 10 Hrs, which is 24% of the study population surveyed. Questions 15-24 were purposed to bring the awareness knowledge of the respondents towards electromagnetic radiation of the cellular phones and it can be arbitrarily said that a score of 5 or more means that the person is aware. The average of the correct responses to each of the 10 questions given by the ENT practitioners is 5.97±1.66. Similarly, questions 25 to 35 assess the awareness of health hazards produced by mobile phone radiation. The mean correct response of the Otorhinolaryngologists is 6.30±1.87.